2016
DOI: 10.1098/rspb.2015.2724
|View full text |Cite
|
Sign up to set email alerts
|

Trophic complexity in aqueous systems: bacterial species richness and protistan predation regulate dissolved organic carbon and dissolved total nitrogen removal

Abstract: Loading of water bodies with dissolved organic carbon (DOC) and dissolved total nitrogen (DTN) affects their integrity and functioning. Microbial interactions mitigate the negative effects of high nutrient loads in these ecosystems. Despite numerous studies on how biodiversity mediates ecosystem functions, whether and how diversity and complexity of microbial food webs (horizontal, vertical) and the underlying ecological mechanisms influence nutrient removal has barely been investigated. Using microbial microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…With the results of C mic as well as total phospholipid-derived fatty acids from Chang and Chiu [16] in a parallel study, C mic content was found the highest in cedar plantation soils. This finding could be evidence that increasing S b OC content benefits microbial growth [32]. Moreover, C mic content was positively correlated with S b OC content and TOC in this study, so S b OC content may be derived from the decomposition of soil TOC as a result of microbial activity [32].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…With the results of C mic as well as total phospholipid-derived fatty acids from Chang and Chiu [16] in a parallel study, C mic content was found the highest in cedar plantation soils. This finding could be evidence that increasing S b OC content benefits microbial growth [32]. Moreover, C mic content was positively correlated with S b OC content and TOC in this study, so S b OC content may be derived from the decomposition of soil TOC as a result of microbial activity [32].…”
Section: Discussionsupporting
confidence: 55%
“…This finding could be evidence that increasing S b OC content benefits microbial growth [32]. Moreover, C mic content was positively correlated with S b OC content and TOC in this study, so S b OC content may be derived from the decomposition of soil TOC as a result of microbial activity [32].…”
Section: Discussionsupporting
confidence: 55%
“…The ECS features a wide gradient of microbial diversity owing to the substantial environmental variations from coastal to oceanic regions [36,37]. Regarding trophic interaction, the grazing effect of nanoflagellates on bacterial biomass has been studied in the ECS [38], and has potentially profound impacts on biogeochemical cycling and energy transfer through the microbial loop [39][40][41]. Clear biodiversity effects on the trophic interaction between protist and bacterial communities had been examined in laboratory experiments [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…During the application of bacterial monocultures and mixtures, we used the substitutive experimental design to determine the impact of bacterial species richness on bacterial abundance and plant performance (Saleem et al, 2016a). While our bacterial species diversity level was simple (monoculture vs. mixture of three species); nevertheless, it has sufficient range to provide valuable insights into microbial interactions and their impacts on the plant-microbe performance.…”
Section: Methodsmentioning
confidence: 99%